THE PROBLEM OF LIBERALIZING ISLAMIC MARRIAGE LAW IN INDONESIA : The Perspective of Science Philosophy - Athoillah Islamy (AL-SYAKHSHIYYAH Jurnal Hukum Keluarga Islam dan Kemanusiaan, 2020)
The phenomenon of liberalism on Islamic marriage law in Indonesia often creates social problems. Therefore, it is important to understand understanding and wise attitudes towards the phenomenon within the framework of the scientific paradigm. This research aims to understand various forms of liberalism on Islamic marriage law in Indonesia in the perspective of the philosophy of Science. This research is a qualitative research in the form of literature review. The type of legal research in this study is philosophical normative legal research. The research data used is various research on liberalism on the law of Islamic marriage in the Compilation of Islamic Law (KHI). Meanwhile, the theory used as a knife of analysis is the theory of the scientific revolution of Thomas Samuel Kuhn. This study concludes that liberalism on Islamic marriage law in Indonesia is a form of paradigm shift over the construction of legal thinking in various KHI articles that are considered to have experienced anomalies, which are not relevant to social development and do not answer the challenges of modernity, such as issues of gender equality, democracy, human rights Humans, and pluralism. Such conditions have encouraged contemporary Islamic law reviewers in Indonesia to voice a paradigm shift and even a scientific revolution by giving birth to the construction of new Islamic marriage law.